1991
DOI: 10.1109/42.108593
|View full text |Cite
|
Sign up to set email alerts
|

Entropic contrast enhancement

Abstract: A technique for the contrast enhancement of a picture is proposed. The method is derived from the entropy concept of information theory. The originality of the algorithm rests on the use of a local contrast to define the digital entropy. The basic idea of the treatment is to enhance the contrast by transforming the global entropy. The same technique can also be used for an adaptive smoothing processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…There are some implementing problems using local information measure from work [11]. A.Beghdadi and A.Khellaf [12] worked with (4) as a criterion to decide a pixel is corrupted or not.…”
Section: B Problems With Local Information Measurementioning
confidence: 99%
“…There are some implementing problems using local information measure from work [11]. A.Beghdadi and A.Khellaf [12] worked with (4) as a criterion to decide a pixel is corrupted or not.…”
Section: B Problems With Local Information Measurementioning
confidence: 99%
“…Since the pioneer work of Frieden [9], the use of entropy [10], [11] in image analysis has attracted a great number of researchers, especially in image reconstruction [12], [13] and segmentation [14], [15]. In our previous work [16] that followed the idea of Shiozaki [17], which consists in defining a local entropy and thus performing a local treatment, we have shown that by amplifying the local entropy of the contrast, one can get a contrasted image. It has also been suggested that a noisefiltering treatment can be obtained by decreasing the entropy of the local contrast in a given neighborhood.…”
Section: Introductionmentioning
confidence: 97%
“…Contrast enhancement is an important area especially in image recognition and related fields. Traditionally, contrast enhancement has been realized by a proper selection of wavelet filters, enhancement functions (Fan and Laine, 1996), multimodal histograms (Grundland and Dodgson, 2006), entropy operators (Khellaf et al, 1991), to name a few.…”
Section: Introductionmentioning
confidence: 99%